In Vitro Analysis of Antioxidant, Anticancer, and Bioactive Components of Apocynum venetum Tea Extracts - Chong Li; Guangbin Huang; Fang Tan; Xianrong Zhou; Jianfei Mu; Xin Zhao (Journal of Food Quality)
The dry leaf of Apocynum venetum tea extracts (AVTEs) belonging to the Apocynaceae family is a traditional Chinese medicine. The aim of this study is to identify the bioactive components of AVTE and analyse its antioxidant and anticancer activity in vitro. Method. Flavones and polyphenols in AVTE were determined by high-performance liquid chromatography (HPLC) assay. The scavenging capacity of tea extracts to 1,1-diphenyl-2-picrylhydrazyl (DPPH); 2,2′-azino-bis-(3-ethylbenzthiazoline-6-sulfonic acid) diammonium salt (ABTS); hydroxyl (OH); and superoxide anion-free radicals were investigated by spectrophotometry. We also detailed the cytotoxicity assay of AVTE (50, 100, and 200 μg/mL) to human embryonic kidney 293T cells, the protective effect of AVTE on 293T cells induced by hydrogen peroxide (0.3 mmol/L), and the anticancer effect against the human hepatoma HepG2 cells via 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazolium bromide (MTT) assay. We investigated the antioxidative effects of AVTE in human embryonic kidney 293T cells and the anticancer mechanism in HepG2 human hepatoma cells via quantitative real-time reverse transcription-polymerase chain reaction (RT-qPCR) assay. Results. HPLC analysis showed that AVTEs contain neochlorogenic acid, chlorogenic acid, rutin, isoquercetin, isochlorogenic acid B, astragalin, isochlorogenic acid C, rosmarinic acid, quercetin, and trans-cinnamic acid. These extracts have high antioxidant activity and dose-dependent relation through free radical scavenging experiments. The cell viability of 293T cells treated with hydrogen peroxide (0.3 mmol/L) was significantly lower than that of normal cells, and the cell viability of oxidatively stressed 293T cells after AVTE (50, 100, and 200 μg/mL) treatment was significantly improved (P<0.05). Moreover, cytotoxicity experiments showed that the survival rate of 293T cells was over 90%, but the proliferation of HepG2 cells was significantly inhibited in a dose-dependent manner by AVTE. Furthermore, cytoprotective effects in 293T cells were induced via upregulation of glutathione peroxidase (GSH-Px), GSH, superoxide dismutase (SOD), and catalase (CAT) antioxidant-related factors, as well as apoptosis in HepG2 cells was induced via upregulation of caspase-3, caspase-9, p21, and p53 apoptosis-associated factors, as assessed via mRNA expression levels after treatment with AVTE, which were consistent with the results of antioxidant gene detections. As a conclusion, AVTE appears to be an effectively functional drink, due to its rich functional components and antioxidant and anticancer activities.